2020
DOI: 10.1002/hed.26325
|View full text |Cite
|
Sign up to set email alerts
|

Added value of metastatic cervical lymph node group V in nodal staging of nasopharyngeal cancer

Abstract: Background Prognostic significance of posterior cervical lymph node metastasis in nasopharyngeal cancer is largely unknown. This study aims to determine the added prognostic significance of cervical lymph node group V to the standard American Joint Committee on Cancer (AJCC) staging system (eighth edition AJCC) of nasopharyngeal patients with cancer treated with intensity‐modulated radiation therapy (IMRT) in terms of overall survival (OS), distant metastatic‐free survival (DMFS), and disease‐free survival (DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…More and more studies have found that the presence of nodal metastases is one of the key factors that predict patients at risk of distant metastases. These studies have gone further to investigate the prognostic values of nodal characteristics in detail [42][43][44][45][46]. Necrosis is easily observed in metastatic nodes from NPC but very rarely in primary tumour (about 2%) on the pre-treatment staging MRI [34].…”
Section: Discussionmentioning
confidence: 99%
“…More and more studies have found that the presence of nodal metastases is one of the key factors that predict patients at risk of distant metastases. These studies have gone further to investigate the prognostic values of nodal characteristics in detail [42][43][44][45][46]. Necrosis is easily observed in metastatic nodes from NPC but very rarely in primary tumour (about 2%) on the pre-treatment staging MRI [34].…”
Section: Discussionmentioning
confidence: 99%